The Influence of Experiential Learning in Field Trip on Career Maturity of Students - Yanuari Srianturi; Yunita Dwi Setyoningsih (Journal of Education and Counseling (JECO), 2023)
The aim of the research to determine the relationship between experiential learning through field trip with career maturity of vocational school student. The research uses quantitative correlation method. The population of research are 10th students of SMK Teuku Umar Semarang consist of 197 students and the sample consist of 120 students with simple random sampling. Data collection method used is the psychological scale and questionnaire.Validity and reliability test use product moment formula and alpha formula. Data were analyzed using descriptive techniques percentage and product moment correlation. Based on the descriptive analysis of the percentage and the product moment correlation indicates that (1) experiential learning in the field trip the students in the high category (2) career maturity of students included in the high criteria, (3) there is correlation between experiential learning through field trip with career maturity of students. Obtained correlation coefficient (rxy) > r table (0,517 > 0,176) with significance = 0,000 and coefficient of determination (R2) or R Square 0,267 = 26,7%. In experiential learning it does not only emphasize thinking processes but also brings together affective and psychomotor experiences through active student learning events.